Flipped learning at University for the development of soft skills - Gülbay, Elif; La Marca, Alessandra (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2018)
The purpose of the research has been to experiment a training methodology with the use of flipped learning. The study involved 236 undergraduate students whose four soft skills (creativity, critical thinking, communication, collaboration) were aimed to get developed and it followed an almost-ex perimental single-group plan using both quantitative and qualitative methods. This made it possible not only to collect more detailed data and information about the processes and the participants but also to follow and define in a more analytical way the actually-designed and realized path, activities and actions. The effectiveness of the experimental action has been measured through a series of specially designed tools that were considered appropriate to validate the hypotheses. The results show that only three months after, there has been an overall improvement in the students and this might positively affect the training action.